Investigation of doping effect on electrical conduction mechanism and Li+ ion insertion/extraction in ZnO-XV2O5 {X=5% and 10%} electrode for superior energy storage application. (November 2021) - Tripathi, Himadri Sekhar; Rudra, Moumin; Mukherjee, Rajesh; Dutta, Alo; Sinha, T.P.
Abstract: In an effort to enhance the electrical conductivity and electrochemical charge storage capacity of pure ZnO, the multivalent V2 O5 is doped with different percentage by solid-state synthesis procedure with low annealing temperature. The materials are characterized by the X-ray diffraction (XRD) and the Fourier Transform Infrared Spectroscopy (FTIR). The XRD pattern reveals hexagonal wurtzite structure with preferred orientation along (101) plane. Three secondary phases Zn3 (VO4 )2, Zn4 V2 O9 and ZnV3 O8 appear after V2 O5 doping. The vibrational bending and stretching modes are identified by the Fourier Transform Infrared Spectroscopy (FTIR). The temperature dependent electrical conduction mechanism of ZnO–V2 O5 (ZNV) varistor ceramic materials is studied by ac impedance spectra analysis. The effect of doping on the electrical conductivity formalism was well discussed. By Nearest Neighbor hopping (NNH) model, it is shown that activation energy of ZnO gradually decreased from 0.28 eV to 0.21 eV by introducing V2 O5 . The electrochemical properties of as prepared ZNV electrodes are investigated by Cyclic voltammetry (CV), Galavanostatic charge-discharge (GCD) and Electrochemical Impedance Spectra (EIS) analysis. In 1 M Li2 SO4 electrolyte the ZnO–10%V2 O5 (ZNV10) shows maximum specific capacitance 447 F/g at current density 1 A/g. The cyclic stability of pure ZnO, ZnO-5% V2 O5 (ZNV5) and ZnO–10%V2 O5 (ZNV10) are tested for 1000 cycles. The capacity retention ratio of pure ZnO increases from 68% to 88% after 10% V2 O5 doping. The charge storage mechanism of ZNV10 is demonstrated by Faradaic adsorption/desorption through the redox charge transfer process. This work may provide a new scope for further development of pseudocapacitor electrode for high performance supercapacitor. Highlights: XRD pattern revealed hexagonal wurtzite structure and three secondary phases Zn3 (VO4 )2, Zn4 V2 O9 and ZnV3 O8 appeared. In 1 M Li2 SO4 electrolyte the ZnO–10%V2 O5 (ZNV10) shows maximum specific capacitance 447 F/g at current density 1 A/g. The capacity retention ratio of pure ZnO develops from 68% to 88% after 10% V2 O5 doping.